Association of clinical symptoms and cardiometabolic dysregulations in patients with schizophrenia spectrum disorders - Zhao, Chenxu; Habtewold, Tesfa Dejenie; Naderi, Elnaz; Liemburg, Edith J.; Bruggeman, Richard; Alizadeh, Behrooz Z. (European psychiatry, 2023)
Patients with schizophrenia spectrum disorders (SSD) have a shortened life expectancy related to cardiovascular diseases. We investigated the association of cognitive, positive, and negative symptoms with cardiometabolic dysregulations in SSD patients. Overall, 1,119 patients from the Genetic Risk and Outcome in Psychosis (GROUP) study were included. Cognitive function, positive and negative symptoms were assessed at baseline, 3-year, and 6-year. Cardiometabolic biomarkers were measured at 3-year follow-up. We used linear and multinomial logistic regression models to test the association between cardiometabolic biomarkers and clinical trajectories and performed mediation analyzes, while adjusting for clinical and demographic confounders. Cognitive performance was inversely associated with increased body mass index (mean difference [β], β = -1.24, 95% CI = -2.28 to 0.20, = 0.02) and systolic blood pressure (β = 2.74, 95% CI = 0.11 to 5.37, = 0.04). The severity of positive symptoms was associated with increased glycated hemoglobin (HbA1c) levels (β = -2.01, 95% CI = -3.21 to -0.82, = 0.001). Increased diastolic blood pressure (OR = 1.04, 95% CI = 1.01 to 1.08, = 0.02; OR = 1.04, 95% CI = 1.00 to 1.08, = 0.048) and decreased high-density lipoprotein (OR = 6.25, 95% CI = 1.81 to 21.59, = 0.004) were associated with more severe negative symptoms. Increased HbA1c (OR = 1.05, 95% CI = 1.01 to 1.10, = 0.024; OR = 1.08, 95% CI = 1.02 to 1.14, = 0.006) was associated with more severe positive symptoms. These associations were not mediated by antipsychotics. We showed an association between cardiometabolic dysregulations and clinical and cognitive symptoms in SSD patients. The observed associations underscore the need for early identification of patients at risk of cardiometabolic outcomes.